How Productivity and Trade Liberalization Can Affect the Economies of Developing Nations is Illustrated by the Vietnamese Manufacturing Sectors Case - Dung, Nguyen Dac (Organizations and Markets in Emerging Economies, 2024)
This article proposes a model to examine the impact of trade liberalization on productivity growth in developing countries, exemplified by Vietnam, which is positioned at a technological distance from the frontier. Built upon the Schumpeterian framework and Total Factor Productivity (TFP) analysis, the study illustrates that free trade can directly influence the technological gap of a small developing nation by necessitating the importation of all intermediate goods from its dominant trading partner, a developed country. Moreover, trade liberalization has a negative impact on Vietnam’s productivity growth, with domestic competition and trade barriers emerging as significant factors. Additionally, the research concludes that the national economic policies of Vietnam during the 2016–2020 period were ineffective, partially attributed to the failure of state-owned enterprises. As a result, international trade openness may lead to enduring adverse consequences for smaller developing countries, like Vietnam, and serves as a noteworthy example of diminishing innovation.
Keywords: trade liberalization; open economy macroeconomics; productivity growth; WTO; Vietnamese manufacturing